Pengaruh Media Komik Terhadap Prestasi Belajar Fisika Siswa - Fartina Fartina; Tsamarul Hizbi; Laxmi Zahara; Zaotul Wardi; Deti Septia Wardika (Universitas Hamzanwadi, 2022)
This study aims to determine the effect of Comic Media on student achievement on the subject of straight motion material. This type of research uses a quantitative approach with a pre-experimental design method. The population in this study were students of class X IPA at MA Darul Iman NW Karang Baru for the academic year 2022/2023. While the sampling used in this study is a Saturated Sampling Technique. The class that was sampled in this study was class X IPA which only consisted of one class as an experimental class without a comparison class or control class because this study used one group pre-test and post-test. The instrument of this research is in the form of a student's achievement test, which consists of pretest and posttest questions. The results showed that Comic Media can affect student achievement on the subject of straight motion. This can be proven by the results of the data hypothesis test, namely where (0,05 > 0,231) which means that it is accepted and rejected.